Design and Synthesis of Aza‐Bicyclononene Dienophiles for Rapid Fluorogenic Ligations. Issue 10 (25th January 2018) - Siegl, Sebastian J.; Vázquez, Arcadio; Dzijak, Rastislav; Dračínský, Martin; Galeta, Juraj; Rampmaier, Robert; Klepetářová, Blanka; Vrabel, Milan
Abstract: Fluorogenic bioorthogonal reactions enable visualization of biomolecules under native conditions with excellent signal‐to‐noise ratio. Here, we present the design and synthesis of conformationally‐strained aziridine‐fused trans ‐cyclooctene (aza‐TCO) dienophiles, which lead to the formation of fluorescent products in tetrazine ligations without the need for attachment of an extra fluorophore moiety. The presented aza‐TCOs adopt the highly strained "half‐chair" conformation, which was predicted computationally and confirmed by NMR measurements and X‐ray crystallography. Kinetic studies revealed that the aza‐TCOs belong to the most reactive dienophiles known to date. The potential of the newly developed aza‐TCO probes for bioimaging applications is demonstrated by protein labeling experiments, imaging of cellular glycoconjugates and peptidoglycan imaging of live bacteria. Abstract : Super‐reactive dienophiles : Fusion of an aziridine ring to trans ‐cyclooctenes was found to enhance their reactivity while still maintaining good stability under biological conditions. These aza‐TCOs lead to the formation of fluorescent products upon reaction with 1, 2, 4, 5‐tetrazines, which is useful for bioimaging applications.